Hydrodynamic Fluidic Pump Empowered Sensitive Recognition and Active Transport of Hydrogen Peroxide in 1D Channels - Shuya Liu; Yongxian Guo; Yanjun Gong; Yanze Wei; Qiongzheng Hu; Li Yu (Advanced Science)
Abstract Through synthetic chemistry, the development of molecular devices for the precise selective recognition and active transport of small molecules stands as one of the most ambitious objectives in extensive medical, environmental, and biological applications. The periodical channels of the metal–organic frameworks (MOFs) with excellent chemical affinity offer vast regulatory space for reaching this goal. Herein, by post‐modifying fluorescent probes and ionic liquid molecules into the Zr‐MOFs (NU‐1000), a donor–acceptor (D‐A) system within the periodical 1D channels is created to construct a hydrodynamic fluidic pump within the abundant 1D channels. Irradiation with light serves to initiate and direct fluid motion, expediting the transport of H2O2 molecules to the active site, thus boosting the sensor sensitivity through gas enrichment. The rapid mass transfer, characterized by a high flow rate and intensified interaction between the D‐A system and H2O2 molecules, enables the detection of H2O2 at concentrations as low as 20 ppb. Besides, with the aid of incident light, the pump system exhibits active transport characteristics by transporting radicals derived from H2O2 against a concentration gradient, reaching a remarkable 10th cycle. The strategy of achieving active transport of small molecules through pore modification holds promise for advancing the development of artificial bioactive channels.